Analysis of Extreme Hydrometeorological Events - Bonaccorso, Brunella; Peres, David J. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Extreme hydrometeorological events, which cause severe impacts in terms of injuries, casualties, and socioeconomic losses, are being reported more and more frequently worldwide. Climate variability and anthropogenic changes amplify the impacts of these events. This reprint showcases studies which address challenges related to monitoring, modeling, forecasting, and assessing the impacts of hydrometeorological hazards. These studies focus on: (i) the description of recent relevant extreme hydrometeorological events, accompanied by analyses of spatiotemporal features and trends; (ii) the estimation and projection of the impacts of climate change and land-use transformations on the occurrence and severity of hydrometeorological extreme events, with associated uncertainties; (iii) the integration of remote sensing data or climate forecasts and models to provide timely warnings or reliable predictions; and (iv) the use of advanced statistical methodologies to characterize extreme hydrometeorological events, among other topics.